Transculturalism in Tan Twan Engs the gift of rain - Wen, Lee Ng; Mani, Manimangai; Wan Yahya, Wan Roselezam (SciPress, 2016)
While the growing body of research on Tan Twan Eng’s The Gift of Rain (2009) focuses on the protagonist, Philip Hutton’s traumatic condition, his Chinese identity, and his ambiguous identity, this study devotes particular attention to the complexity of interactions between various cultures practised by Philip. This study aims to address this gap by applying the concept of transculturalism to analyse the processes of acquiring a foreign culture and incorporating the foreign culture into traditional cultures experienced by Philip. In other words, this study employs the concept of transculturalism to examine multicultural depictions in the novel. Scholars, such as Khan, Tiwari, Sheoran and Tan C. S. who have examined multicultural depictions in various literary texts, have found that multicultural circumstances cause certain ethnic groups to lose their cultures and identities. Hence, the multicultural circumstances depicted are perceived as negative phenomena. However, this study has found that by examining the interactions between various cultures, rather than focusing on the end products such as portrayals of hybridity, the positive sides of multicultural depictions could be revealed. The transculturation process experienced by Philip shows that the new cultural practices he has created are made up of both his traditional cultures and the foreign culture he has acquired. This means that Philip does not totally lose his traditional cultures and identities. Therefore, this study concludes that multicultural depictions in The Gift of Rain could be read positively, provided that the interactions between various cultures, which resulted in the incorporation of a foreign culture into traditional cultures, are examined.